Lattice response of the porous coordination framework Zn(hba) to guest adsorption. (2nd August 2017) - Auckett, Josie E.; Dharma, A. David; Cagnes, Marina P.; Darwish, Tamim A.; Abrahams, Brendan F.; Babarao, Ravichandar; Hudson, Timothy A.; Robson, Richard; White, Keith F.; Peterson, Vanessa K.
Abstract : Analysis of in situ neutron powder diffraction data collected for the porous framework material Zn(hba) during gas adsorption reveals a two-stage response of the host lattice to increasing CO2 guest concentration, suggesting progressive occupation of multiple CO2 adsorption sites with different binding strengths. The response of the lattice to moderate CH4 guest concentrations is virtually indistinguishable from the response to CO2, demonstrating that the influence of host–guest interactions on the Zn(hba) framework is defined more strongly by the concentration than by the identity of the guests.